SOME PROBLEMS AND ISSUES OF SUSTAINABLE MANAGEMENT OF MANGROVE ECOSYSTEMS OF TAMIL NADU, INDIA - Fernando, Olivia J.; Pandian, Ponnammal K. (Journal of Indian Fisheries Association, 2015)
Mangrove forests, which are found along a substantial portion of the coastlines in the tropics, are fast disappearing by reclamation for aquaculture, farming, residential and industrial development and non-sustainable harvesting of timber. They play an important role in supporting tropical estuarine and coastal food webs, by providing a major source of organic material and acting as nursery grounds and habitats for commercially important fish species. For a variety of reasons relating to human activities, large areas of mangrove forests are being lost or threatened with disruption. Mangrove, a tidal wetland, is a good example of complex land and water system whose resource attributesÂ· is neither fully understood from an ecological perspective nor valued comprehensively in economic terms. With increased ecological and social perception of the functions of wetlands, the utility and relative values will increase. The perception, however, varies from society to society. It must be recognized that mangrove forests differ greatly in local conditions and in their ability to produce a wide variety of economic products. What may be highly productive strategy for one country may have little meaning to its neighbour. Therefore, it becomes essential that from among diversity of potential uses of the mangrove environment, specific uses will have to be decided, and management plan developed on site, or area specific basis. It is therefore necessary to arrive at a balance between the views of the ecologists and economists on the management of mangroves. Biological conservation should encompass resource management in the sense that integrity of the biological and physical attributes of the resource base should be sustained and man-induced management practices should not alter an ecosystem to the extent that biological production is eliminated. Sustained yield management for food, fiber and fuel would serve to sustain local fisheries while generating new economic enterprises. This requires the recognition of mangrove environment as a resource with economic value, and managed according to local conditions and national priorities. Keywords: Mangrove ecosystem, Sustainable Management